Marketing Strategies Used by Chilean Enterprises to Increase customer lifetime value - Farías Nazel, Pablo C. (Cuadernos de Administración, 2014)
The purpose of this work was to report an exploratory investigation that seeks to contribute to knowledge on the way companies are using marketing strategies to increase customer value. The focus of the investigation is Chilean enterprises. The results show that the marketing strategies used by Chilean enterprises present a significant customer orientation; however, they are more inclined to follow passive marketing strategies in each of the three processes analyzed to increase customer value. The fact that an important proportion of the enterprises analyzed develop passive strategies raises the opportunity for these enterprises and potential competitors to analyze the feasibility of conducting more active and scientific strategies to approach their clients.